Psychopathy and the perception of the genuineness of facial expressions. (March 2022) - Glenn, Andrea L.; Efferson, Leah M.; Kastner, Rebecca M.; Johnson, Alexandria K.; Remmel, Rheanna J.
Abstract: Individuals with psychopathic traits are thought to have deficits in emotion recognition, yet they are also known for being manipulative and conning, a skill that necessitates sensitivity to social cues. One unanswered question is whether psychopathic individuals can recognize subtleties in the expression of emotion, such as whether an expression is genuine or not. We examined relationships between psychopathy and ratings of the "genuineness" of pictures of facial expressions. Undergraduate participants ( n  = 453; 32.5% identifying as men) completed the Triarchic Psychopathy Measure and the Self-Report Psychopathy Scale III. They viewed images that depicted faces displaying either fake (forced, posed) or genuine expressions of happiness, sadness, surprise, and fear and rated how fake versus real they thought the expression was. Controlling for gender, psychopathic traits on both measures were associated with making less of a distinction between fake and real images. Individuals higher in psychopathy rated genuine expressions as less real than those lower in psychopathy. Analyses of psychopathy factors revealed a distinct finding for Boldness (interpersonal dominance and fearlessness), which was associated with rating real smiles as more real. Overall, the findings suggest that individuals higher in psychopathy may perceive the sincerity of emotions differently, which may influence their social behavior. Highlights: Psychopathy was associated with less distinction between real and posed expressions. Boldness was associated with rating genuine smiles as more genuine. The sincerity of emotional expressions may be perceived differently in psychopathy.